The Influence of Innovation and Product Quality on Consumer Purchasing Decisions (Survey of Toyota Avanza Car Consumers in Padang City) - Bimas Saputra, Ebit; M, Agussalim (Greenation Research & Yayasan Global Resarch National, 2023)
This research aims to determine the relationship between product innovation variables, product quality and purchasing decisions. The current research aims to find out whether product innovation and product quality influence purchasing decisions. Based on these objectives, the type of research carried out is hypothesis testing. This research uses quantitative methods. This analysis aims to determine the differences between the independent variables and the dependent variable. The analytical tools used in this research are Excel software and the Statistical Program for Social Science (SPSS 25.0) to determine differences between variables and obtain percentages and frequencies of respondent data. From the results of research 1. there is a positive and significant influence between Product Innovation on Purchasing Decisions for Toyota Avanza Car consumers. 2. There is a positive and significant influence of product quality on purchasing decisions for Toyota Avanza car consumers.